2019
DOI: 10.1111/jvim.15626
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of urinary or fecal incontinence in dogs with thoracolumbar acute non‐compressive nucleus pulposus extrusion

Abstract: Background: Urinary (UI) and fecal (FI) incontinence occur in up to 7.5% and 32% of dogs, respectively, after thoracolumbar acute noncompressive nucleus pulposus extrusion (ANNPE).Hypotheses/Objectives: To investigate clinical, diagnostic, and therapeutic predictors of UI and FI in dogs with ANNPE affecting the T3-L3 spinal cord segments.Animals: Hundred and eighty-seven dogs with T3-L3 ANNPE diagnosed based on clinical and MRI findings.Methods: Multicenter retrospective study. Data were obtained from medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
(59 reference statements)
0
20
1
Order By: Relevance
“…In ANNPE, dogs with a smaller lesion had a shorter interval to unassisted ambulation. In contrast, a percentage cross sectional area that equals or exceeds 90% of the spinal cord had a 92% chance of having an unsuccessful long-term outcome (38), and a lesion exceeding 40% of the transverse area has been associated with an increased likelihood of long-term urinary and fecal incontinence (22). However, a low-field MRI study of 21 dogs with ANNPE found no association between any MRI parameter with outcome (71).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 95%
See 3 more Smart Citations
“…In ANNPE, dogs with a smaller lesion had a shorter interval to unassisted ambulation. In contrast, a percentage cross sectional area that equals or exceeds 90% of the spinal cord had a 92% chance of having an unsuccessful long-term outcome (38), and a lesion exceeding 40% of the transverse area has been associated with an increased likelihood of long-term urinary and fecal incontinence (22). However, a low-field MRI study of 21 dogs with ANNPE found no association between any MRI parameter with outcome (71).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 95%
“…As such, these cases are scarcely reported in the literature and it is extremely difficult to establish what their prognosis would be if managed long term. There is a recent report of three dogs with ANNPE that recovered walking, but none recovered fecal continence and 2/3 remained urinary incontinent (22). A review of the literature on FCEM revealed seven dogs in this category for which long term outcomes were available; three of the seven recovered ambulation but there is no information on their continence (24).…”
Section: Recovery In Animals With No Dppmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this clinical trial recruited dogs with Hansen type 1 intervertebral disc herniation in which spinal shock is less common than in more severe cases, moreover, the majority had only moderately severe injuries, again making spinal shock unlikely. In another study on thoracolumbar acute non-compressive nucleus pulposus extrusion, a weak association was found between spinal shock and the odds of remaining faecally incontinent, although this likely reflects an association between spinal shock and severity of injury ( 24 ). Interestingly, bladder atony at the time of spinal shock can be improved with functional electrical stimulation of sacral nerve roots in experimental dogs ( 25 , 26 ) when delivered early in the disease process.…”
Section: Consequences Of Spinal Cord Injury On Micturitionmentioning
confidence: 99%